KONSEP ADAB MENURUT KH. HASYIM ASY'ARI DALAM KITAB ADAB AL-'ALIM WA AL-MUTA'ALLIM DAN RELEVANSINYA TERHADAP PENDIDIKAN AGAMA ISLAM - Suniati; Akhmad Zaeni; Ainun Zahro Hidayati; Nur Rofi’ah; Firda Maghfirotus Sholihah (PT. Hasba Edukasi Mandiri, 2026)
This study examines the concept of adab (Islamic ethics and proper conduct) according to KH. Hasyim Asy'ari as presented in his book Adab al-'Alim wa al-Muta'allim and its relevance to contemporary Islamic Religious Education (Pendidikan Agama Islam). The research employs a qualitative approach using the library research method. Primary data were obtained from Adab al-'Alim wa al-Muta'allim, while secondary data were collected from scholarly journals, books, and other relevant literature. Data were analyzed through collection, classification, interpretation, and conclusion drawing. The findings reveal that KH. Hasyim Asy'ari considers adab to be the fundamental principle of the educational process. Students are expected to possess sincerity, humility, discipline, respect for teachers, and commitment to practicing knowledge, while teachers are required to demonstrate sincerity, exemplary character, justice, and moral responsibility. These ethical values foster meaningful learning and contribute to the development of noble character. Furthermore, the concept of adab remains highly relevant to addressing contemporary educational challenges, including moral degradation, declining respect for teachers, and the growing emphasis on cognitive achievement over character formation. Therefore, integrating KH. Hasyim Asy'ari's concept of adab into Islamic Religious Education can strengthen character education and promote the development of intellectually competent, morally responsible, and spiritually grounded learners.